2014
DOI: 10.5194/acp-14-12195-2014
|View full text |Cite
|
Sign up to set email alerts
|

OH-initiated heterogeneous oxidation of tris-2-butoxyethyl phosphate: implications for its fate in the atmosphere

Abstract: Abstract. A particle-phase relative rates technique is used to investigate the heterogeneous reaction between OH radicals and tris-2-butoxyethyl phosphate (TBEP) at 298 K by combining aerosol time-of-flight mass spectrometry (C-ToF-MS) data and positive matrix factor (PMF) analysis. The derived second-order rate constants (k2) for the heterogeneous loss of TBEP is (4.44 ± 0.45) × 10−12 cm3 molecule−1 s−1, from which an approximate particle-phase lifetime was estimated to be 2.6 (2.3–2.9) days. However, large d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 79 publications
4
27
0
Order By: Relevance
“…Furthermore, Li et al have revealed that RH could retard the reaction rate of •OH initiated heterogeneous oxidation of gaseous TCIPP and subsequently hindered the gaseous TCIPP degradation, implying the varied concentrations upon different humidity conditions (Li et al, 2017a). A significant negative correlation was observed between RH and particulate TBOEP (p b 0.05, Table S9), which is consistent with the finding that increased RH promotes TBOEP degradation via decreasing the viscosity of particle (Liu et al, 2014a;Liu et al, 2019). However, other hydrophilic OPEs including TCIPP and TCEP, the two important chlorinated OPEs with higher detection rates and measured concentrations in this study, did not possess a similar trend, indicating that the effect of RH may be obscured by other influence factors such as a more significant positive correlation with temperature of TCEP.…”
Section: Influence Factors Ofsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, Li et al have revealed that RH could retard the reaction rate of •OH initiated heterogeneous oxidation of gaseous TCIPP and subsequently hindered the gaseous TCIPP degradation, implying the varied concentrations upon different humidity conditions (Li et al, 2017a). A significant negative correlation was observed between RH and particulate TBOEP (p b 0.05, Table S9), which is consistent with the finding that increased RH promotes TBOEP degradation via decreasing the viscosity of particle (Liu et al, 2014a;Liu et al, 2019). However, other hydrophilic OPEs including TCIPP and TCEP, the two important chlorinated OPEs with higher detection rates and measured concentrations in this study, did not possess a similar trend, indicating that the effect of RH may be obscured by other influence factors such as a more significant positive correlation with temperature of TCEP.…”
Section: Influence Factors Ofsupporting
confidence: 81%
“…Water (i.e., RH) can influence the OH-initiated heterogeneous oxidation of TBOEP via influencing the phase of particles, subsequently influence the mixing state and reactivity (Liu et al, 2014a;Liu et al, 2019). Furthermore, Li et al have revealed that RH could retard the reaction rate of •OH initiated heterogeneous oxidation of gaseous TCIPP and subsequently hindered the gaseous TCIPP degradation, implying the varied concentrations upon different humidity conditions (Li et al, 2017a).…”
Section: Influence Factors Ofmentioning
confidence: 99%
“…S1 and S2 in the Supplement. The gas-phase reactions were conducted in the OFR, a detailed description of which has been presented elsewhere (Liu et al, 2014b). Before entering into the OFR, gasphase species were mixed thoroughly in the mixing tube.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that RH can positively or negatively influence reactions between OH and the organic particles. Some researchers have observed that increased RH will lower the viscosity of the amorphous aerosol particles and subsequently enhance OH uptake because particle-phase diffusion is feasible, [78][79][80] whereas other results show that the OH uptake was suppressed at higher RH because of competitive co-adsorption of water, which will take up the reactive sites. 52 Based on our previous study, degradation of levoglucosan by OH was influenced significantly by RH because of different layers of water cover on the surface of levoglucosan under different relative humidities.…”
Section: Effect Of Relative Humiditymentioning
confidence: 99%